Factors of code-switching among bilingual international students in Malaysia - Muthusamy, Paramasivam; Muniandy, Rajantheran; Kandasamy, Silllalee.S.; Hassan @ Hussin, Omrah; Subramaniam, Manimaran; Farashaiyan, Atieh (Sciedu Press, 2020)
The present study aims to identify the factors that can potentially affect code switching in a college classroom in Malaysia. The participants were twenty bilingual international students enrolled in an English course in Malaysia. The data were collected through semi-structured interviews with the participating students. The findings of the study indicated that the main factor behind code switching among the students was incompetence in the second language. Other factors that could account for code switching were maintaining privacy, the ease of speaking in the first language compared to speaking in English, avoiding misunderstanding, and unfamiliarity with similar words in English. Therefore, code switching was found to be an effective strategy used by the students to make their intended meaning explicit and to transmit some knowledge to other students in classroom interactions. This study provides some implications for English teaching community including language learners, teachers, and curriculum developers.